The role of γ-C 2H 5NO 2 as a new transient liquid phase in cold sintering process of BaTiO 3 composites - Jitrawan Noisak; Pimchanok Ieamviteevanich; Thitirat Charoonsuk; Phakkhananan Pakawanit; Nattapong Pinpru; Wanwilai Vittayakorn; Tosapol Maluangnont; Panpailin Seeharaj; Theerachai Bongkarn; Te-Wei Chiu; Naratip Vittayakorn (My University, 2024)
Dielectric materials, like barium titanate-based (BT-based), have excellent dielectric properties but require high temperatures (above 1300 ˚C) for ceramic fabrication, leading to high costs and energy loss. The cold sintering process (CSP) offers a solution to these issues and is gaining worldwide attention as an innovative fabrication route. In this work, we proposed an alternative organic ferroelectric phase, gamma-glycine (γ-GC) that acts as a transient liquid phase to fabricate high-density composites with barium titanate (BT) at low-temperature through a CSP. Our findings show that the density of 15γ-GC/85BT reached 96.7±1.6% when sintered at 120 ˚C for 6 hours (h) under 10MPa uniaxial pressure. The SEM-EDS mapping of the composite suggested that γ-GC completely underwent the precipitation-dissolution process and, therefore, filled between BT particles. Moreover, XRD and FTIR confirmed the preservation of γ-GC without the undesired phase transformation. In addition, the ferroelectric and dielectric properties of the γ-GC/BT composites were reported. The high dielectric constant (εr) was 3600, and the low dielectric loss (tan δ) was 1.20 at 200 ˚C, 100 kHz, with 15γ-GC/85BT composite. The hysteresis loop showed a remanent polarization (Pr) of 0.55 µC.cm-2 and a coercive field (Ec) of 7.25 kV.cm-1. Our findings reaffirmed that organic ferroelectric material (γ-GC) can act as a transient liquid phase in a CSP that can successfully and sustainably fabricate γ-GC/BT composites at low temperatures while delivering outstandingly high performance.
Keywords: Liquid phase; Transient (computer programming); Ferroelectric and Piezoelectric Materials